Outpatient satisfaction with the integration of primary health care services: A comparative study in Gowa Regency - Andi Afriyani Safitri; Fais Satrianegara; Fatmawaty Mallapiang (Science Midwifery, 2026)
The implementation of Primary Healthcare Integration aimed to address service fragmentation and improve the quality of health services in Indonesia. This study evaluated outpatient satisfaction with the integrated system compared to a conventional service model in Gowa Regency. A quantitative comparative research design was employed, involving 100 respondents from a health center implementing the integration and 97 respondents from a health center using the conventional model. Data were collected through questionnaires measuring five dimensions of service quality: reliability, responsiveness, assurance, empathy, and tangibles. Statistical analysis using the Mann-Whitney U test revealed a significant difference in satisfaction levels between the two groups (p < 0.001). The integrated system group showed a substantially higher mean rank of 144.08 compared to 52.53 in the conventional group. High satisfaction levels were observed across all dimensions in the integrated system, particularly in the empathy and tangible aspects. It was concluded that the lifecycle-based cluster approach within the integrated system significantly enhanced patient experience and satisfaction. These findings suggested that the transformation of primary health services effectively met community expectations and provided a more structured healthcare delivery model.